1999
DOI: 10.1177/00220345990780031301
|View full text |Cite
|
Sign up to set email alerts
|

The Optimum Time to Initiate Habitual Xylitol Gum-chewing for Obtaining Long-term Caries Prevention

Abstract: Habitual xylitol gum-chewing may have a long-term preventive effect by reducing the caries risk for several years after the habitual chewing has ended. The goal of this report was (1) to determine if sorbitol and sorbitol/xylitol mixtures provide a long-term benefit, and (2) to determine which teeth benefit most from two-year habitual gum-chewing - those erupting before, during, or after habitual gum-chewing. Children, on average 6 years old, chewed gums sweetened with xylitol, sorbitol, or xylitol/sorbitol mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 13 publications
1
57
1
12
Order By: Relevance
“…The long-term effects of chewing sugarfree gum were demonstrated by Hujoel et al, 34 five years after the two year Belize chewing gum programme ended. In this blind follow-up study, xylitol gum had reduced the caries risk by 59% and sorbitol gum by 35%, compared with a no gum group.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 92%
“…The long-term effects of chewing sugarfree gum were demonstrated by Hujoel et al, 34 five years after the two year Belize chewing gum programme ended. In this blind follow-up study, xylitol gum had reduced the caries risk by 59% and sorbitol gum by 35%, compared with a no gum group.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 92%
“…20 The results are similar to those obtained by the clinical studies following the use of a xylitol and sorbitol mixture containing chewing gum. 12,13 Present study unique as hitherto no similar studies have been reported in literature. Results of this study showed combination of sorbitol and xylitol dentifrices was most effective against S. mutans and Lactobacillus, hence the use of it may be promoted further in the dentifrices which can make the dentifrice cost effective.…”
Section: Discussionmentioning
confidence: 56%
“…Study carried out by the Hujoell, Makinen on acid production in the oral cavity from sorbitol in the presence of xylitol in chewing gum containing sorbitol reduces acid production from sorbitol. 13 This may be explained by the following effects of xylitol as: Reduction of plaque and the number of microorganisms on the teeth which are a consequence of the toxic effect of xylitol-5-phosphate and inhibition of acid production from sorbitol due to competitive blocking of the phosphotransferase system due to structural similarities between xylitol and sorbitol. 17 Hence combination of xylitol and sorbitol can be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Hujoel et al [23] presented a long-term reduction of caries-risk as the result of xylitol chewing gum use. After administration to 6-year-old children for 2 years of chewing gum with xylitol, sorbitol or a mixture of xylitol and sorbitol, they found after 5 years a 59% reduction in caries risk in the xylitol group and 44% in the xylitol-sorbitol group.…”
Section: Prevention Of Caries Development In Permanent Teeth In Childrenmentioning
confidence: 99%